Effects of periodic robot rehabilitation using the Hybrid Assistive Limb for a year on gait function in chronic stroke patients. (October 2021) - Tanaka, Hiroki; Nankaku, Manabu; Kikuchi, Takayuki; Nishi, Hidehisa; Nishikawa, Toru; Yonezawa, Honami; Kitamura, Gakuto; Takagi, Yasushi; Miyamoto, Susumu; Ikeguchi, Ryosuke; Matsuda, Shuichi
Highlights: About 30% of stroke survivors have some obstacles to walking even in chronic phase. Robot rehabilitation has attracted attention for the last several decades. The long-term HAL training improves gait function in stroke patients over a year. Abstract: Using a robot for gait training in stroke patients has attracted attention for the last several decades. Previous studies reported positive effects of robot rehabilitation on gait function in the short term. However, the long-term effects of robot rehabilitation for stroke patients are still unclear. The purpose of the present study was to investigate the long-term effects of periodic gait training using the Hybrid Assistive Limb (HAL) on gait function in chronic stroke patients. Seven chronic stroke patients performed 8 gait training sessions using the HAL 3 times every few months. The maximal 10-m walk test and the 2-minute walking distance (2MWD) were measured before the first intervention and after the first, second, and third interventions. Gait speed, stride length, and cadence were calculated from the 10-m walk test. Repeated one-way analysis of variance showed a significant main effect on evaluation time of gait speed (F = 7.69, p < 0.01), 2MWD (F = 7.52, p < 0.01), stride length (F = 5.24, p < 0.01), and cadence (F = 8.43, p < 0.01). The effect sizes after the first, second, and third interventions compared to pre-intervention in gait speed (d = 0.39, 0.52, and 0.59) and 2MWD (d = 0.35, 0.46, and 0.57) showed a gradual improvement of gait function at every intervention. The results of the present study showed that gait function of chronic stroke patients improved over a year with periodic gait training using the HAL every few months.